Altered Visual Plasticity in Morbidly Obese Subjects - Lunghi, Claudia; Daniele, Giuseppe; Binda, Paola; Dardano, Angela; Ceccarini, Giovanni; Santini, Ferruccio; Prato, Stefano Del; Morrone, Maria Concetta (iScience, 2019)
Growing evidence indicates a close link between energy metabolism and neural plasticity as obesity is associated with alterations of cognitive functions, memory, and hippocampal neurogenesis. However, it is still unknown whether obesity can affect low-level sensory plasticity. Here we investigated this issue by probing early visual plasticity induced by short-term (2 h) monocular deprivation in a group of adult volunteers with a wide range of Body Mass Index (BMI), from normal weight to morbid obesity. We found that the effect of monocular deprivation decreased with increasing BMI, and morbidly obese subjects (BMI>40) failed to show the homeostatic plasticity effect seen in normalweight participants. In addition, morbidly obese subjects exhibited altered binocular rivalry dynamics compared with normal-weight observers. These results show for the first time that the impact of obesity observed at the neural and cognitive level extends to basic sensory processing and plasticity.